Systematic Review and Meta-Analysis of the Clinical Utility of the ADOS-2 and the ADI-R in Diagnosing Autism Spectrum Disorders in Children. - Lebersfeld, Jenna B.; Swanson, Marissa; Clesi, Christian D.; O'Kelley, Sarah E. (Journal of Autism & Developmental Disorders, 2021)
The Autism Diagnostic Observation Schedule, Second Edition (ADOS-2) and the Autism Diagnostic Interview, Revised (ADI-R) have high accuracy as diagnostic instruments in research settings, while evidence of accuracy in clinical settings is less robust. This meta-analysis focused on efficacy of these measures in research versus clinical settings. Articles (n = 22) were analyzed using a hierarchical summary receiver operating characteristics (HSROC) model. ADOS-2 performance was stronger than the ADI-R. ADOS-2 sensitivity and specificity ranged from.89-.92 and.81-.85, respectively. ADOS-2 accuracy in research compared with clinical settings was mixed. ADI-R sensitivity and specificity were.75 and.82, respectively, with higher specificity in research samples (Research =.85, Clinical =.72). A small number of clinical studies were identified, indicating ongoing need for investigation outside research settings.